Strategy for Maintenance Cost Effectiveness of Fixed Plant Assets by using Life Cycle Cost Analysis and Monte Carlo Simulation to Achieve Production Targets of 2015 – 2021 at The Coal Processing and Handling Division (The Indonesian Journal of Business Administration, 2015)
Abstract.The objective of this research is removing under performances in coal flow process at CPHD division KPC to achieve production target by using cost effective maintenance strategy. Performance gap analysis for existing eight assets during first quarter 2015 reveals that three assets running in below performance against the target. Therefore, the research focuses on the three failure assets. There are two alternative strategies, do nothing or upgrade.For both strategies are developed by using Monte Carlo Simulation to estimate reliability of the assets and Life Cycle Cost (LCC) model to find out annual cash outflow respectively during the life time of the assets, 2015 until 2021, the end of Coal Contract of Work (CCOW). Finally, Net Present Cost (NPC) analysis is developed to find out the lowest long term cost of ownership for both strategies. KPC produce three types of coal quality; 1) Prima, 2) Pinang and 3) Melawan since the beginning of production in 1991. Since 2013, KPC had been producing only the last two coals, because Prima coal reserve naturally diminished.The failure assets will cause the KPC unable to achieve the production target at the end of 2015 which amounted to 2,149,002 tons. The failure of asset is primarily because the existing assets were not designed for pinang and melawan quality, this leads to higher breakdown maintenance which will decrease capability of assets to perform its function.The result of the research recommends that CPHD should upgrade the failure assets to accommodate pinang and melawan coals. Therefore, KPC is able to achieve the production target of 2015 until 2021.Keywords: Cost effective maintenance, LCC, Monte Carlo simulation